Federalismo e competências tributárias, uma geografia dos impostos - Fabricio Gallo; René Somain; Martine Droulers (Confins)
Analysing the evolution process of Brazilian federalism (result, among other things, of different Constitutions and tax collection policies) is one way to understand the complexity of the national territory. In this country, the fiscal architecture of federalism requires the imposition of rules that create and regulate tensions between the entities, and distribution mechanisms and redistribution of resources between federal agencies therefore become very important to allow more or less autonomy to public administration. As federal agencies have the power to legislate, they are in constant tension, which always implies the emergence of new political arrangements, given that municipal and State budgets are limited (especially for small municipalities and poor States) which makes them dependent on transfers from other entities, in particular of the Union. The following sequence of maps outlines the distribution and transfer of taxes in the composition of current revenues of the entities that make up the Brazilian federation.